Changes in the prevalence of overweight/obesity and adiposity among pre-school children in Kraków, Poland, from 2008 to 2018. Issue 6 (6th November 2020) - Żegleń, Magdalena; Kryst, Łukasz; Kowal, Małgorzata; Woronkowicz, Agnieszka; Sobiecki, Jan
Abstract: Socioeconomic changes occurring over time influence the lifestyle choices of a population, and these can significantly affect children's body weight and composition. The aim of this study was to assess the changes in prevalence of overweight, obesity and adiposity in pre-school children in Poland between 2008 and 2018. Body height, body weight and subscapular and triceps skinfolds were measured in 2167 children aged 3–7 years from Kraków. Body mass index and adiposity (percentage body fat, %BF) were calculated for the children, who were then categorized as underweight, normal weight, overweight or obese according to Cole's cut-off points. Adiposity was categorized according to the z -scores for %BF as low (<−1), normal (−1 to 1) or high (>1). Differences between cohorts were analysed using the chi-squared test. Only the decrease in the prevalence of obesity in 5-year-old girls was found to be statistically significant. However, some overall tendencies were noted. Decreases in the prevalence of underweight, overweight and obesity were observed for both sexes, as well as in the incidence of high adiposity in boys and low adiposity in girls. Increases in the prevalence of high adiposity in girls and low adiposity in boys were also noted. There was no significant change in the prevalence of overweight and obesity among pre-school children over the study decade, and the visible tendencies included decreases in the prevalence of excess body weight and adiposity as well as underweight and low body fat. Also, the visible trends in adiposity were mostly negative. Further studies should, however, also consider the levels of physical fitness and activity of children, as these have a crucial influence on the measured characteristics.